Effectiveness of Improved Use of Chewing Gum During Capsule Endoscopy in Decreasing Gastric Transit Time: A Prospective Randomized Controlled Study - Huang, Liang; Hu, Yue; Chen, Fang; Liu, Shan; Lu, Bin (Frontiers in Medicine, 2021)
Background/Aim: Chewing gum throughout small bowel capsule endoscopy (SBCE) increases completion rates (CRs) but decreases small bowel transit time (SBTT) and diagnostic yield (DY). We determined the effects of chewing gum early during SBCE on gastric transit time (GTT), SBTT, CR, DY, and gastroscopy intervention. Methods: We prospectively enrolled patients (ages 16–80 years) undergoing SBCE between January and June 2019. Patients were randomized to a chewing gum group (103 patients) and a control group (102 patients). Patients in the former group chewed one piece of gum for 15 min every 30 min during the first hour of SBCE. Two gastroenterologists blinded to the study group examined the data. Results: GTT was shorter in the chewing gum group (29.0 min, interquartile range: 17.0–52.0 min) than in the control group [42.5 min (23.25–60 min); P = 0.01]. SBTT was similar in the two groups [318.5 min (239.5–421.3 min) vs. 287.0 min (216.0–386.0 min); P = 0.08]. Gastroscopy rate was lower in the chewing gum group (15.53 vs. 32.35%, P = 0.005). CR (95.15 vs. 89.22%, P = 0.114) and DY (67.96 vs. 59.80%, P = 0.224) did not differ between the groups. The number of abnormal-lesion types detected per patient was higher in the chewing gum group [1.0 (0.0–2.0) vs. 2.0 (0.0–2.0); P = 0.049]. Conclusions: Chewing gum early during SBCE significantly reduced GTT and gastroscopy intervention, with no influence on SBTT (Trial number: NCT03815136).